2021
DOI: 10.1080/0886022x.2021.1963774
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl fumarate ameliorates endotoxin-induced acute kidney injury against macrophage oxidative stress

Abstract: Background Characterized by macrophage infiltration, renal inflammation during septic acute kidney injury (AKI) reveals a ubiquitous human health problem. Unfortunately, effective therapies with limited side effects are still lacking. This study is aiming to elucidate the role of Dimethyl fumarate (DMF) in macrophages against oxidative stress of septic AKI. Methods Balb/c mice were gavaged by 50 mg/kg DMF then injected with 10 mg/kg LPS by i.p. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…It has been shown that nuclear factor erythroid-2-related factor 2 (Nrf2) is a key transcription factor that modulates the expression of antioxidant enzymes, including catalase and SOD [ 56 ]. Previous studies have shown that Nrf2 activation can serve as a useful therapeutic approach for septic AKI [ 57 , 58 , 59 ]. Interestingly, hispidulin can activate Nrf2-dependent antioxidant systems to suppress oxidative stress [ 19 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that nuclear factor erythroid-2-related factor 2 (Nrf2) is a key transcription factor that modulates the expression of antioxidant enzymes, including catalase and SOD [ 56 ]. Previous studies have shown that Nrf2 activation can serve as a useful therapeutic approach for septic AKI [ 57 , 58 , 59 ]. Interestingly, hispidulin can activate Nrf2-dependent antioxidant systems to suppress oxidative stress [ 19 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Malate is an intermediate in the citric acid cycle, and increased malate activity has been reported in cisplatin-induced kidney dysfunction that may be a repair mechanism for malate ( 26 ). Fumarate is converted from succinic acid and, like other TCA cycle metabolites, its regulation in kidney disease appears to be dynamic ( 27 29 ). Pyruvate is a key mediator of aerobic and anaerobic energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Dimethyl fumarate, an example of this category, led to reduction in myocardial infarct size in animal models of myocardial ischemia/reperfusion injury and to prevention of atherosclerosis in apoE −/− mice [ 152 , 153 ]. This agent may ameliorate nephrotoxicity due to various causes in in vivo animal models [ 154 , 155 , 156 , 157 ]. Moving to Nox inhibition, the dual Nox1/4 inhibitor setanaxib (GKT137831) has been investigated in the experimental setting of doxorubicin-, angiotensin II-, and hypertension-induced cardiac remodeling, displaying cardioprotective effects based on antioxidant and antifibrotic action [ 158 , 159 , 160 ].…”
Section: Clinical Implications and Future Directionsmentioning
confidence: 99%